Interferences and interventions after acute myocardial infarction: an integrative review of the literature - Oliveira Júnior, Vicente Alves de; Hamaji, Mariana Pereira; Sousa, Fernando Henrique; Sousa, Carla Aparecida Pinto de; Valenti, Vitor Engrácia [UNESP] (My University, 2013)
Objective: to identify the interference of acute myocardial infarction (AMI) in the quality of life of affected, interventions and understanding by health professionals. Method: an integrative review, aiming to answer << What are the interference in the quality of life of post-AMI customers? >> and << What are the interventions proposed in order to minimize them? >>. We selected 12 articles available in the LILACS database, between 2000 and 2011, based on the criteria of inclusion and exclusion. Results: we have selected a total of 12 articles selected according to the inclusion and exclusion criteria pre-established. We obtained a classification into two themes (1) interference with quality of life and (2) proposals for interventions to minimize interference. Conclusions: highlights the importance of patient involvement in care plan well structured, multidisciplinary team integration and quantity of publications by heterogeneous country on the subject.

Objetivo: identificar as interferências do infarto agudo do miocárdio (IAM) na qualidade de vida dos acometidos, as intervenções e sua compreensão pelos profissionais de saúde. Método: revisão integrativa, objetivando responder << Quais as interferências na qualidade de vida dos clientes pós IAM? >> e << Quais as intervenções propostas com vistas a minimizá-las? >>. Selecionou-se 12 artigos disponíveis na base de dados LILACS, entre 2000 e 2011, baseado nos critérios de inclusão e exclusão. Resultados: foram selecionados ao todo 12 artigos selecionados de acordo com os critérios de inclusão e exclusão pré- estabelecidos. Obtivemos um classificação em dois temas (1) interferências na qualidade de vida e (2) propostas de intervenções visando minimizar as interferências. Conclusão: destaca-se a importância do envolvimento do paciente no plano de cuidado bem estruturado, integração da equipe multiprofissional e quantidade de publicações heterogênea pelo país sobre o assunto.

Objetivo: identificar la interferencia de infarto agudo de miocardio (IAM) en la calidad de vida de los afectados, las intervenciones y la comprensión por los profesionales de la salud. Método: revisión integradora, con el objetivo de responder a << ¿Qué es la interferencia en la calidad de vida de los clientes post-IAM? >> y << ¿Cuáles son las intervenciones propuestas con el fin de minimizarlos? >>. Se seleccionaron 12 artículos disponibles en la base de datos LILACS, entre 2000 y 2011, con base en los criterios de inclusión y exclusión. Resultados: se han seleccionado un total de 12 artículos seleccionados de acuerdo con los criterios de inclusión y exclusión previamente establecidos. Se obtuvo una clasificación en dos temas (1) interferencia con la calidad de vida y (2) las propuestas de intervenciones para reducir al mínimo la interferencia. Conclusiones: destaca la importancia de la participación del paciente en el cuidado plan bien estructurado, la integración del equipo multidisciplinario y la cantidad de publicaciones por país heterogéneo sobre el tema.
Interferências e intervenções pós-infarto agudo do miocárdio: revisão integrativa de literatura
Las interferencias e intervenciones después de un infarto agudo de miocardio: una revisión integradora de la literatura